Physical Compatibility of Ibuprofen Lysine Injection with Selected Drugs During Simulated Y-site Injection - Holt, Robert J. (Pediatric Pharmacy Advocacy Group, 2008)
PURPOSE: To study the physical compatibility of ibuprofen lysine injection (NeoProfen, Ovation Pharmaceuticals Inc., Deerfield, IL) with medications commonly used in the premature neonatal population during simulated Y-site administration. MATERIALS AND METHODS: Commonly used intravenous medications in preterm infants were evaluated for physical compatibility with ibuprofen lysine injection. A 20-mL sample of ibuprofen lysine drug product solution was mixed with a 20-mL sample of each of the 34 medications at concentrations used clinically. The mixtures were stored at room temperature and each sample was evaluated for turbidity and physical appearance at time 0 (immediately after preparation) and at 4 hours after preparation. RESULTS: The following drugs were deemed compatible with ibuprofen lysine: ceftazidime, epinephrine, furosemide, heparin lock flush, diluted insulin, morphine sulfate, phenobarbital, potassium chloride, and sodium bicarbonate. Diluted dopamine was initially compatible at time 0 but showed a small precipitate at the 4-hour time point. CONCLUSION: Of the 37 drug solutions tested, 14 preparations (10 medications; several with more than one diluent) showed physical compatibility with ibuprofen lysine, 1 was compatible at time 0 and incompatible at 4 hours, and 1 could not be evaluated. The remaining preparations were considered to be incompatible.